PENGARUH PENGGUNAAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Aulia Ika Wulandari; Bambang Suteng Sulasmono (Universitas Pakuan, 2020)
RELATIONSHIP BETWEEN MOTIVATION WITH ORGANIZATIONAL COMMITMENTThe purpose of this research was to re-analyze the use of the learning approach of Realistic Mathematic Education in increasing the learning outcome of an elementary school student. The research method was a meta-analysis. The research began with formulated the problem and then collect exiting research data that was already though Google Scholar. The research data found 9 articles and 2 mini-thesis from the relevant Repository. The research results from the researcher were analyzed by quantitative comparison methods. Base on the results of the analysis, that learning approach of Realistic Mathematics Education could improve student’s learning from the lowest 21,33% to the highest 61,09% and the mean was 32,22%.